A contribution to the study of diet of Formative societies in North-western Argentina: isotopic and archaeological evidences - Calo, Cristina Marilin (2009)
The present paper is aimed at presenting and discussing currently available isotopic values (d13C) of human samples dated to the Formative Period in the Santa María Valley, adjacent to the Yungas and Puna regions of northwestern Argentina. Results show that the expected tendency of increasingly positive C4 isotopic values consistent with the hypothesis of maize agriculture consolidation during Formative times was only partially corroborated. A fuller understanding of this trend is limited by the scant number of samples as well as by the lack of local reference values. Notwithstanding, the revision of this evidence in light of relevant archaeobotanical data allows us to start building a more accurate reconstruction of the lifestyles of early agricultural societies settled in northwestern Argentina.